Prevalence of caries and DMF-T index with D1-D2 scale on students - Harahap, Setunggal Agung Nugroho; Susilawati, Sri; Sutardjo, Dede (Padjadjaran Journal of Dentistry, 2013)
Introduction: Many factors associated with poor health habits are initiated during adolescence. This is because as a teenager they have the feeling that they are unique and invulnerable that makes them think that the disease or disorder will not enter into their lives. Based on this, teenagers can have a bad habit for their oral health, thus increasing the level of caries in their mouths. The purpose of this study was to get data on the caries experience (DMF-T index) with D1-D2 scale on students. Method: This type of research is descriptive. The technique used in this sampling is simple random sampling, the sample is 266 students consisting of 109 men and 157 women. Prevalence rate of caries adjusted with 2004 Household Health Survey and DMFT category based on World Health Organization. Result: The results showed that the prevalence of caries in college students of Al-Ihsan Islamic boarding school is 90.6%. DMF-T index in college students of Al-Ihsan Islamic boarding school is 4.18. D1 scale that was found was 280 cases. D2 is the scale found 335 cases. and dental caries were found at 949 cases. Conclusion: Prevalence of caries and DMF-T index with D1-D2 scale on students are prevalence of dental caries is higher than prevalence in 2004 Household Health Survey. DMF-T index is  moderate, while the D1 scale found 280 cases and the D2 scale found 335 cases.